Student Autonomy in Secondary Schools: The Potential for Development - A.V. Rusakova (Moscow State University of Psychology and Education, 2022)
This article explores the potential for the development of student autonomy in a modern Russian comprehensive school. Despite extensive evidence of the importance of teachers' support for school autonomy in foreign studies and the global trend towards the development of an initiative and conscious position of schoolchildren in relation to learning, for the Russian psychology of education, the question of the value and practices of such support from teachers is currently insufficiently reflected. Studies on the adaptation of schoolchildren during the transition to distance learning in the context of the pandemic also confirm the relevance of self-learning skills, self-organization and autonomous learning motivation for successful learning in conditions of uncertainty. However, there is a significant shortage of research in the field of the content and prevalence of autonomy support practices in Russian schools. Experts representing twelve Russian general education schools located in various regions of Russia and positioning themselves as developing the autonomy of adolescents or interested in its development were invited to participate in the presented search study. 12 semi-structured interviews were conducted, the thematic analysis of which made it possible to identify the main ways of interpreting the concept of autonomy in the educational process, the benefits of supporting autonomy in learning, a list of key barriers preventing its support, as well as to describe a set of psychological and pedagogical practices to support the autonomy of schoolchildren implemented by school specialists. The necessity of transformation of the educational discourse in the direction of increasing the autonomy of schoolchildren and the dissemination of relevant ideas and practices in the pedagogical community is substantiated.